2011
DOI: 10.1002/bjs.7268
|View full text |Cite
|
Sign up to set email alerts
|

Abdominal trauma in primary blast injury

Abstract: Abdominal PBI is uncommon but has the potential for significant mortality and morbidity, which may present many days after blast exposure. It is commoner after blast in enclosed spaces and under water.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
26
0
14

Year Published

2011
2011
2020
2020

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(40 citation statements)
references
References 83 publications
0
26
0
14
Order By: Relevance
“…A primary blast wave inflicts the gas-containing organs, such as ears, lungs, and intestinal organs, and may be overlooked by most clinicians if not military affiliated (11). Pulmonary primary blast injury may be evident upon presentation or may manifest as late as 48 hours from the time of the explosion (12).…”
Section: Discussionmentioning
confidence: 99%
“…A primary blast wave inflicts the gas-containing organs, such as ears, lungs, and intestinal organs, and may be overlooked by most clinicians if not military affiliated (11). Pulmonary primary blast injury may be evident upon presentation or may manifest as late as 48 hours from the time of the explosion (12).…”
Section: Discussionmentioning
confidence: 99%
“…When a high-explosive detonates (such as gelignite, trinitrotoluene, C4 or Semtex), an increase in air pressure is created, known as an overpressure or blast wave, which travels supersonically up to 8000 m/s (Cullis, 2001). This overpressure attains its peak pressure in the first few milliseconds following the blast (Owers et al, 2010), and can reach pressures of 20-30 kbar, where 1 kbar is 1000 times atmospheric pressure (Kocsis and Tessler, 2009). As the blast wave expands, the energy of the blast wave dissipates and the pressure decreases.…”
Section: The Nature Of Blastmentioning
confidence: 97%
“…Cho et al (2010) conducted a study of 133 combat casualties with colonic injuries, and found 71% acquired injuries through the blast wave and fragmentation, reflecting the use of IEDs. However, abdominal injury is less common than lung injury (Owers et al, 2010), and not as common as extremity wounds (Barker, 2001).…”
Section: Primary Blast Injuries (Pbis)mentioning
confidence: 98%
See 2 more Smart Citations